KEKUATAN PEMBUKTIAN TANDA TANGAN ELEKTRONIK DALAM KONTRAK BISNIS (Jurnal De Jure Muhammadiyah Cirebon, 2024)
The development of information technology has changed the way business transactions are carried out, including the use of electronic signatures in business contracts. This research examines the evidentiary power of electronic signatures in business contracts in Indonesia from a legal perspective. The research method used is normative juridical with a statutory and conceptual approach. The research results show that electronic signatures have legal force and valid legal consequences as long as they meet the requirements stipulated in Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) as amended by Law Number 19 of 2016. Signature A qualified electronic signature has equivalent evidentiary power as a conventional signature. This research concludes that although electronic signatures have strong legal evidentiary power, care is needed in their implementation to ensure their validity and admissibility as evidence in court.Keywords: Electronic Signature, Business Contract, Evidentiary Power.